مبدأ الديمقراطية التشاركية في الجماعات المحلية - بن عدي, وليد; برجوح, أيوب; بقار, فـــــاتــح (University of Eloued جامعة الوادي, 2023)
قد وصلنا في نهاية دراستنا هذه التي تطرقنا فيها إلى الإطار المفاهيم الديمقراطية التشاركية والجماعات المحلية وآليات تطبيقها، وقد تبين لنا من خلال ما تطرقنا إليه واعتمدنا من مصادر ومراجع أن المشرع الجزائري قد حرص على و وضع نصوص قانونية تتماشى مع التحولات والجذرية التي شهدتها الإدارة في الدولة الجزائرية في إدارتها الإقليمية، وذلك باعتبار أن الديمقراطية التشاركية جاءت لتغطي الخلل الناجم عن الديمقراطية التمثيلية. وقد لاحظنا أيضا أن المشرع الجزائري أكد على تطبيق وتكريس الديمقراطية التشاركية في الجماعات المحلية وذلك بالرجوع للقانون رقم 07/12 في قانون الولاية وأيضا القانون رقم 10/11 في قانون البلدية، وهذا من أجل أن يفتح الطريق أمام المواطنين للمشاركة الديمقراطية على المستوى المحلي. اسفرت تجربة الديمقراطية التشاركية في الجزائر على انها وسيلة جيد من اجل إعادة الثقة بالسلطة والنظام الحاكم ، فمن اهم اسس التي تقوم عليها هي فتح باب الحوار بين المواطن والسلطة ، مما يبعث روح المسؤولية للموطنين وتقديمه المبادرات الفعلية من اجل تحسين الخدمة العمومية، ومن جانب اشراك المواطن في صنع القرار حول المسائل المتعلقة بالتنمية المحلية. We have reached the end of our study, in which we touched on the framework of participatory democratic concepts, local groups, and the mechanisms for their implementation. It has become clear to us, through what we have discussed and relied upon from sources and references, that the Algerian legislator has been keen to develop legal texts that are consistent with the radical transformations that the administration has witnessed in the state. Algeria in its regional administration, given that participatory democracy came to cover the defect resulting from representative democracy. We have also noted that the Algerian legislator emphasized the application and consecration of participatory democracy in local communities by referring to Law No. 07/12 in the state law and also Law No. 10/11 in the municipal law, in order to open the way for citizens to participate democratically at the local level. The experience of participatory democracy in Algeria has resulted in it being a good way to restore confidence in the authority and the ruling system. One of the most important foundations on which it is based is opening the door to dialogue between the citizen and the authority, which inspires a spirit of responsibility to citizens and presents actual initiatives in order to improve public service, and on the part of citizen involvement. In decision-making on matters related to local development.
مذكرة ماستر
Keywords: الديمقراطيةالتشاركية، الديمقراطيةالتمثيلية، الجماعاتالمحلية; :.Participatorydemocracy , Representativedemocracy And local groups.